Like a fish in water: Habitus adaptation mechanisms of informal tourism entrepreneurs in Thailand. (September 2021) - Çakmak, Erdinç; Lie, Rico; Selwyn, Tom; Leeuwis, Cees
Abstract: This article investigates possible pathways of habitus change by informal tourism entrepreneurs in Thailand. Bourdieu's concept of habitus is depicted as a person's understanding of the world. Do people adapt their worldview in response to only external stimuli? Through ethnographic fieldwork including participant observations and active semi-structured interviews with 53 participants, this paper identifies a classification of four modes of habitus adaptation: (1) Understanding and appreciating the field and its conditions, (2) Challenging core beliefs systems, (3) Applying a practical sense to 'objective possibilities', and, (4) Challenging non-reflective dispositions. We argue that charting the modes of habitus adaptation could help policymakers understand the change processes of informal entrepreneurs in the tourism sector and their willingness to change. Highlights: Developing and extending Bourdieu's theory of habitus into tourism Charts the modes of habitus adaptation by informal tourism entrepreneurs in Thailand Demonstrates the relational structures between habitus and field at tourism destinations Advocates a change in one's radical beliefs happens only if a combination of major changes in one's social context and individual life trajectory takes place Makes policy recommendations for assessing stakeholders' willingness to change